2019
DOI: 10.1002/ajh.25630
|View full text |Cite
|
Sign up to set email alerts
|

Shortening the ex vivo culture of CD19‐specific CAR T‐cells retains potent efficacy against acute lymphoblastic leukemia without CAR T‐cell‐related encephalopathy syndrome or severe cytokine release syndrome

Abstract: S.T. and R.H. managed the patients and wrote the manuscript. Z.G. collected the data. LD revised the manuscript. C.S., X.Z. and C.Y. contributed to patient management. L.Z. produced the figures and Table. Y.H. participated in the registration of the clinical research. J.Y. and Z.L. were responsible for clinical trial recruitment and data revision. J.D. performed flow cytometry detection and bone marrow cell morphology detection. P.C. was responsible for the statistical analysis. Y.S.L. produced CAR T-cells. L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…In this study, 67% of patients had an objective response, which was consistent with previously reported results. The results of this trial and our previous trial prove the effectiveness and potential of our 4th-generation CAR-T cells (18). In addition, CD27, a costimulatory molecule, is not inferior to 4-1BB, OX40 and ICOS.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In this study, 67% of patients had an objective response, which was consistent with previously reported results. The results of this trial and our previous trial prove the effectiveness and potential of our 4th-generation CAR-T cells (18). In addition, CD27, a costimulatory molecule, is not inferior to 4-1BB, OX40 and ICOS.…”
Section: Discussionsupporting
confidence: 63%
“…The individualized CAR-T cells were produced as previously described (18). Briefly, peripheral blood mononuclear cells of eligible participants were obtained through apheresis and transported to Geno-Immune Medical Institute, Shenzhen, China, where the CAR-T product was manufactured.…”
Section: Manufacture and Infusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, performance status, previous allogeneic hematopoietic stem cell transplantation (HSCT) or blinatumomab treatment and the dose of infused CAR T cells did not show any significant effects on long-term survival [23,35]. However, in a clinical trial carried out in our department, we found that elderly patients were at an increased risk of disease relapse or progression, which requires a further study to confirm the relation between age and relapse risk [37].…”
Section: Predictive Factors For Positive Relapse In Clinical Practicementioning
confidence: 61%
“…4SCAR T-cells can be depleted when uncontrollable toxicity is observed following CAR T-cell infusion. The details of the CART manufacturing process are as previously described (17). The safety and efficacy of 4SCAR T-cells have been demonstrated in patients with highly resistant B-cell lymphoma (18, 19).…”
Section: Introductionmentioning
confidence: 99%